El desarrollo psicosocial de niños con trastorno de déficit de atención con hiperactividad de 5to año básica - Hernández Ayala, Angie Mailyn (2024)
In educational contexts, the psychosocial aspect is fundamental seen from the point of view of caring for students with ADHD. Teachers, for their part, do not use strategies adapted to the needs of these students, which is why this study used a type of descriptive research with a qualitative approach to analyze psychosocial development in the improvement of attention deficit hyperactivity disorder (ADHD). in children in the fifth year of basic education. The methodology used included direct observations of students in the classroom, observations of the teacher, and interviews to collect data on behavior, pedagogical practices, and perceptions related to ADHD. The observations revealed a variety of behaviors and attitudes in the children, from difficulties maintaining attention to skills in teamwork and expressing emotions appropriately. On the other hand, observations of the teacher indicated the implementation of adapted pedagogical strategies, although with a certain lack of consistency in their application. The interviews provided additional information about the challenges faced by the teacher when working with children with ADHD and the strategies used to support their academic and social-emotional development. Areas of improvement were identified in the implementation of adapted pedagogical strategies and in collaboration with parents to establish personalized support strategies. In conclusion, the study highlighted the complexity of ADHD and the importance of comprehensive approaches that address both the academic and social-emotional needs of these children to promote their well-being and optimal development.